Religion and law in independent India / edited by Robert D. Baird - Baird, Robert D. (ed.) (New Delhi, 1993)
Religion and Law in Independent India is a major contribution to the interface between religion and law in independent India. It is a multidisciplinary volume including essays by jurists, legal scholars, historians of religions, political scientists and Sanskritists. Moreover, it is the result of a cooperative international project. Most of the papers were first read at a conference hosted by The University of lowa (U.S.A.) which included eminent scholars from India, Canada and the United States. This volume addresses a wide range of issues and should stimulate further research in this important and neglected area.
Keywords: Religions India 1947-93